Potensi selada air (Nasturtium officinale R. Br) sebagai antioksidan dan agen anti proliferasi terhadap sel MCF-7 secara in vitro - Rahman, Dewi Rahmayani; Rimbawan, Rimbawan; Madanijah, Siti; Purwaningsih, Sri (Jurnal Gizi dan Pangan, 2017)
This study aimed to determine the potential of watercress extract as an antioxidant and antiproliferation against cancer cells in vitro. Cells used in this study were breast cancer culture cells (MCF-7) and vero cells. Watercress was extracted using water solvent and 70% ethanol. Phytochemical test was performed on both types of extract. Toxicity test was measured using BSLT method, assessment of antioxidant activity was measured using DPPH method and inhibitory proliferation in cancer cell was measured using MTT Assay method. Analysis of the data using ANOVA, if there is a significant difference between treatments will be followed up with Duncan test. The results of phytochemical tests showed that watercress extracts had bioactive content namely flavonoids, tannins, saponins, and steroids. The result of BSLT test showed that the strongest extract toxicity was 70% ethanol extract with LC50 value of 406.02 ppm and had the highest antioxidant activity with IC50 value of 102.26 ppm, while proliferation inhibitory test found in MCF-7 breast cancer cells had IC50 value of 1.696 μg / ml and not toxic to vero cells. Result showed that the ethanolic extract of Nasturtium Officinale gave a significant effect on MCF-7 breast cancer cells inhibition (p=0,015) at concentration 50, 400, 800 and 1000 ppm. The mechanism of proliferative inhibition was associated with phytochemical content present in watercress.